Targeting αvβ3 and αvβ5 integrins inhibits pulmonary metastasis in an intratibial xenograft osteosarcoma mouse model - Gvozdenovic, Ana (Oncotarget, 2016)
Osteosarcoma is an aggressive bone cancer that has a high propensity for metastasis to the lungs. Patients with metastatic disease face a very poor prognosis. Therefore, novel therapeutics, efficiently suppressing the metastatic process, are urgently needed. Integrins play a pivotal role in tumor cell adhesion, motility and metastasis. Here, we evaluated αvβ3 and αvβ5 integrin inhibition with cilengitide as a novel metastasis-suppressive therapeutic approach in osteosarcoma. Immunohistochemical analysis of αvβ3 and αvβ5 integrins expression in a tissue microarray of tumor specimens collected from osteosarcoma patients revealed that αvβ5 integrin is mainly found on tumor cells, whereas αvβ3 is predominantly expressed by stromal cells. In vitro functional assays demonstrated that cilengitide dose-dependently inhibited de novo adhesion, provoked detachment and inhibited migration of osteosarcoma cell lines. Cilengitide induced a decline in cell viability, blocked the cell cycle in the G1 phase and caused anoikis by activation of the Hippo pathway. In a xenograft orthotopic mouse model cilengitide minimally affected intratibial primary tumor growth but, importantly, suppressed pulmonary metastasis. The data demonstrate that targeting αvβ3 and αvβ5 integrins in osteosarcoma should be considered as a novel therapeutic option for patients with metastatic disease.